PENGARUH KOMPENSASI FINANSIAL DAN MOTIVASI TERHADAP PRESTASI KERJA TENAGA PEMASARAN PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK. KANTOR CABANG UTAMA PALU - Maramis, Mariska Rosa (Katalogis, 2018)
The study aims to determine and analyze simultaneous and partial influenceÂ  of financial compensation and motivaton on performance of marketing division at PT. Bank Negara Indonesia (Persero) Tbk of Palu Headquarter. Sample is selected with census technique of 40 marketing staff. Method of analysis is multiple linear regressions. The result shows that financial compensation and motivation simultaneously and partially have significant influence on work performance of marketing staff at PT. Bank Negara Indonesia (Persero) Tbk of Palu Headquarter.